The perceived social and economic impacts of brewpubs in neighborhoods of the Greater Cincinnati region. - Dunay, Morgan Nicole (Kansas State University, 2020)
As communities continue to grow and change, planners are tasked with finding ideas, solutions, and innovation to support renewal, social equity, and economic sustainability. Today Breweries are being hailed as a catalyst for economic development and urban renewal through their efforts in revitalizing large industrial buildings and being community gathering spaces. With investigation of community and economic change in urban neighborhoods through the lenses of breweries, we can learn how breweries have impacted the neighborhoods surrounding them. This pilot study examines the current conditions and perceptions of community members of three neighborhoods in the Greater Cincinnati Region to examine if there is a positive perception of brewpubs within urban neighborhoods.
Keywords: Community; Neighborhood; Brewpubs; Breweries; EconomicPlanning